Mali: Un exemple reproductible? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Une interview de Salifou Diarra, Coordonnateur de l'Observatoire des Marchés Agricoles (OMA) du Mali